A single promoter system co-expressing RNA sensor with fluorescent proteins for quantitative mRNA imaging in living tumor cells. Issue 18 (5th April 2019) - Ying, Zhan-Ming; Yuan, Yue-Yan; Tu, Bin; Tang, Li-Juan; Yu, Ru-Qin; Jiang, Jian-Hui
Abstract : Genetically encoded light-up RNA aptamers afford a valuable platform for developing RNA sensors toward live cell imaging. Abstract : Genetically encoded light-up RNA aptamers afford a valuable platform for developing RNA sensors toward live cell imaging. However, quantitative imaging of intracellular RNAs remains a grand challenge. Here we reported a novel genetically encoded RNA sensor strategy using a plasmid that expresses a splittable fusion of the RNA sensor and the GFP mRNA in an individual transcript using a single promoter system. This splittable fusion design enables synchronous co-expression of the RNA sensor with GFP mRNA while alleviates the interference with correct folding of RNA aptamers due to intramolecular hybridization. This single-promoter system is applied to ratiometric imaging of survivin mRNA in tumor cells. The results reveal that the ratiometric images dynamically correlated with survivin mRNA concentrations and allow quantitative imaging of survivin mRNA in different tumor cells. The RNA sensor strategy may provide a new paradigm for developing a robust imaging platform for quantitative mRNA studies in living cells.